Design and implementation of an automated face detection and recognition system - Gu, Qian. (2008)
This thesis provides accurate and reliable algorithms for face detection, recognition and tracking. The automated system for face recognition and tracking, developed in this work, can be used for application in security, camera-based surveillance, video communication and teleconference.